The Crisis and the Future of the Social State. Remarks in the Light of the Portugal Membership in the Structures of the EU - Abrantes, José João (The Copernicus Journal of Political Studies, 2018)
The financial crisis that has affected Europe became a multi-dimension phenomenon. It has caused changes not only in the macroeconomic sphere, but also in the political and social sphere as well as in the labour law area. And so as an example of the great changes in that matter we can see what happened in Portugal, where most of the more recent legislative measures in the area of employment legislation and labour market (as in general in the area of economic policies) assure the compliance with several obligations foreseen in the Memorandum of Understanding, signed in May 2011 between Portugal, the European Commission, the International Monetary Fund and the European Central Bank. Having all that in mind, author intends to analyze the changes in the Portugal’s labour law caused by the financial crisis.